La rappresentazione della morte nell’islam: ‘Izrā’īl l’Angelo della Morte - Fedele, Valentina (Funes. Journal of narratives and social sciences, 2018)
Islamic eschatology has often focused on two features concerning death: the ineluctability and the fear it generates, especially among believers. This is one of the reasons for the attention paid to the Angel of Death, 'Izrā'īl, and the vain attempts of humanity to escape from him, that has given rise to different elaborations, in religious and non-religious literature, still relevant in Muslim world. The attention to this literature and its representation is itself an instrument for deconstructing public discourses on death and Islam, often monopolized by jihadist martyrdom.